Ocorrência de plantas daninhas em cultivo consorciado de café e nogueira-macadâmia - Silva, Vinícius De Castro [UNESP]; Perdoná, Marcos José; Soratto, Rogério Peres [UNESP]; Negrisoli, Eduardo (Escola de Agronomia e Engenharia de Alimentos/UFG, 2013)
Arborization can benefit coffee plantations by reducing the wind speed and temperature variation in the crop. It is also possible that the incident radiation can affect the weed populations and reduce the need for their control. This study aimed at assessing the weeds population and distribution, in arabica coffee intercropped with three macadamia cultivars, six years after planting, in Dois Córregos, São Paulo State, Brazil. Treatments consisted of a 3x3+1 factorial scheme, i.e., coffee intercropped with three macadamia cultivars (HAES 816, IAC 4-20 and IAC 9-20) and three sampling positions of weeds in the intercropping (in the macadamia tree canopy projection, among the macadamia tree canopies projections and in the single rows), plus an additional treatment (sole coffee). The weeds incidence and control, as well as their phytosociological characterization, were evaluated. For coffee intercropped with macadamia, the weeds occurrence and number of species were smaller than for sole coffee. For the projection in the canopy and among canopies of macadamia trees, there was an average decrease of 82% in the occurrence of weeds, in comparison with the sole coffee. The IAC 9-20 cultivar was more efficient in reducing the occurrence of weeds, when intercropped with coffee, for presenting a taller canopy, with a larger diameter.

A arborização pode beneficiar os cafezais, reduzindo a velocidade dos ventos e a amplitude térmica na cultura. É possível, ainda, que a diminuição na radiação incidente possa influenciar a população de plantas daninhas e diminuir a necessidade de seu controle. Objetivou-se, com este trabalho, avaliar a população e a distribuição de plantas daninhas, na cultura de café arábica consorciado com três cultivares de nogueira-macadâmia, seis anos após o plantio, em Dois Córregos (SP). Os tratamentos consistiram de esquema fatorial 3x3+1, ou seja, café consorciado com três cultivares de nogueira-macadâmia (HAES 816, IAC 4-20 e IAC 9-20) e três locais de amostragem das plantas daninhas no consórcio (na projeção da copa da nogueira-macadâmia, entre as projeções das copas da nogueira-macadâmia e na entrelinha solteira), além de um tratamento adicional (café solteiro). Foram avaliados a incidência e o controle de plantas daninhas, bem como a caracterização fitossociológica. No cultivo de café consorciado com nogueira-macadâmia, a ocorrência e o número de espécies de plantas daninhas foram menores que no cultivo de café solteiro. Na projeção da copa e entre as projeções das copas da nogueira-macadâmia, houve, em média, 82% de redução na ocorrência de plantas daninhas, em comparação ao café solteiro. A cultivar IAC 9-20, por apresentar copa mais alta e de maior diâmetro, foi mais eficiente na redução da ocorrência de plantas daninhas, no consórcio com café.
Occurrence of weeds in coffee intercropped with macadamia
Keywords: Coffea arabica L.; Macadamia integrifolia Maiden & Betche; planta invasora; sombreamento; Coffea arabica L.; Macadamia integrifolia Maiden & Betche; invasive plant; shading